A Study of Students’ Storytelling Ability in Narrative Text at SMKN 1 Painan - Maiziko; Yessy Marzona; Sherly Franchisca (JURNAL ARMADA PENDIDIKAN, 2026)
The objective of this research was to find out the students’ ability and student difficulties in story telling of narrative text. This research was conducted at SMKN 1 Painan, the academic year 2024/2025. The researcher conducted this research based on the finding in the classroom. Many students were not able to speak well in the teaching and learning activities in the classroom. The research used descriptive method. The population in this research was 39 students first grade of SMKN 1 Painan, namely X AKT I and X AKT II. the sample, the researcher used cluster random sampling teqnique and X AKT 1 was selected as a sample with a total of 20 students. The instrument of this research was speaking test. In collecting the data, the researcher used an oral test to know the student’s speaking skill in story telling of narrative text and researcher recorded the stude nt’s speaking performance in order to know how there is speaking ability in story telling of narrative text.